2014
DOI: 10.4236/jmmce.2014.23026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Treatment and Fiber Orientation on the Tensile and Morphological Properties of Banana Stem Fiber Reinforced Natural Rubber Composite

Abstract: A mixture of NaOH and Na 2 SO 3 was used in modification of banana stem fibers (BSF). Unidirectional BSF reinforced natural rubber (NR) lamina composites were made using compression moulding method. The results of the tensile loading in 0˚, 45˚ and 90˚ to the fiber directions of the composite with fiber mass fraction of 30% were studied. Surface modification of the BSF with a mixture of 4% NaOH and 2% Na 2 SO 3 increased the tensile strength and elastic modulus of the composite to 4.03 MPa and 147.34 MPa respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 5 publications
0
3
0
5
Order By: Relevance
“…Las fibras de vástago de plátano fueron tratadas inicialmente con NaOH al 4% y con una solución al 2% de Na 2 SO 3 durante 24 horas, luego estas fibras fueron lavadas con agua destilada y secadas al sol durante 48 horas. Para eliminar cualquier traza de humedad, las fibras se secaron en un horno a 60ºC durante 1 hora (Ezema et al, 2014).…”
Section: Vástago De Plátanounclassified
See 2 more Smart Citations
“…Las fibras de vástago de plátano fueron tratadas inicialmente con NaOH al 4% y con una solución al 2% de Na 2 SO 3 durante 24 horas, luego estas fibras fueron lavadas con agua destilada y secadas al sol durante 48 horas. Para eliminar cualquier traza de humedad, las fibras se secaron en un horno a 60ºC durante 1 hora (Ezema et al, 2014).…”
Section: Vástago De Plátanounclassified
“…Las mezclas del caucho natural fueron elaboradas en un molino de tres rodillos durante aproximadamente 30 minutos, luego se colocaron las fibras del tallo entre dos capas de caucho y entonces se recubrieron con láminas de PET, luego se moldearon por compresión en una prensa hidráulica durante aproximadamente 5 minutos a 150 ° C con una presión de 115 kg / cm 2 (Ezema et al, 2014).…”
Section: Vástago De Plátanounclassified
See 1 more Smart Citation
“…In order to enhance environmental degradability to polyethylene, it must be blended with biodegradable additives or photo-initiators [3]. Blending or addition of natural fillers like palm leaf [4], guayule biomass [5], banana stem fiber [6], grass fiber [7], and coconut shell powder [8] into polymer matrices has been studied and exhibits biodegradability besides of renewability, low cost and low density and so on [9]. However, the main drawback of introducing the natural fillers into the synthetic polymer is the poor compatibility between the natural fillers and the polymer matrix and the poor distribution of the natural fillers throughout the polymer matrix, due mainly to the different polarities between two phases.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by Almeida et al [8] paper that reported a composite reinforced with fibers aligned in one direction have high modulus and strength in the fiber direction and poor mechanical characteristics in the transverse direction. In addition, Ezema et al [9] informed that the composite strength in the longitudinal direction (0 o ) is higher than the transverse direction (90 o ) or other orientations, such as 45 o . Therefore the composite with a fiber orientation from 30 o to 90 o produces a lower tensile strength when compared to resin tensile strength of HDPE of 18.12 MPa.…”
Section: -3mentioning
confidence: 99%